2015
DOI: 10.56890/jpacd.v17i.59
|View full text |Cite
|
Sign up to set email alerts
|

Review of scientific and technical bibliography on the use of Opuntia spp. as forage and its animal validation

Abstract: Several studies have shown the remarkable properties of Opuntia spp., a largely distributedspecies in the world. It has been used as an edible resource, especially in periods of foodshortage, and also as livestock food in arid lands. This review aimed at identifying currentliterature related to Opuntia spp. as forage and its validation through experiences withdomestic and other animals. The literature review was carried out October 3, 2014 using theScopus database. From 5,723 documents, 98 of them were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
0
5
1
Order By: Relevance
“…For 91 years , only 288 documents were indexed (19%); from 1991 to 2015, 81%, where it can be highlighted that 451 (31%) were indexed from 1991 to 2005, and 733 (50%) documents were indexed from 2006 to 2015 (Figure 2). The low number of records observed in this study is lower than the 5,723 detected by Grünwaldt et al (2015), since the SCIE and SSCI databases did not incorporate documents such as articles from peer-reviewed journals that are not considered mainstream: congress abstracts, thesis and patents, among others.…”
Section: Bibliometric Indicators Number Of Documents Publishedcontrasting
confidence: 56%
See 1 more Smart Citation
“…For 91 years , only 288 documents were indexed (19%); from 1991 to 2015, 81%, where it can be highlighted that 451 (31%) were indexed from 1991 to 2005, and 733 (50%) documents were indexed from 2006 to 2015 (Figure 2). The low number of records observed in this study is lower than the 5,723 detected by Grünwaldt et al (2015), since the SCIE and SSCI databases did not incorporate documents such as articles from peer-reviewed journals that are not considered mainstream: congress abstracts, thesis and patents, among others.…”
Section: Bibliometric Indicators Number Of Documents Publishedcontrasting
confidence: 56%
“…Concerning Opuntia, three studies were registered where bibliometric techniques were used. In one of them, carried out by Inglese and Liguri (2010) aspects of biology and ecophysiology were addressed; another one deals with the effect of cactus pear in relation to body weight and cardiovascular risks (Onakpoya et al 2015); and the third contemplates studies about cactus pear used as fodder and its validation in animals (Grünwaldt et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According with Grünwaldt et al (2015) Mexico, together with Brazil, Ethiopia, Tunisia and United States have made an important contribution of studies regarding the use of Opuntia in animal production. Recent studies in Brazil and Mexico showed that the addition of cactus pear in diets for small ruminants is useful as supplement feedstuff, as it reduces feed cost without reducing the production and quality of meat and milk.…”
Section: Liveweight Gainmentioning
confidence: 99%
“…Cactus plants comprise succulent botanically articulated stems called nopal pads or cladodes composed of polysaccharides that allow the plant to retain water. Cladodes of nopal are of substantial commercial value as human food and cattle feed (Grünwaldt et al, 2015). However, nopal cacti have other value-added uses, such as being sources of ingredients for cosmetics and pharmaceuticals, being substitutes for flour, and in the production of biofuels (El-Mostafa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%